Inorganic nanowire based solar cells - Fu, Kunwu. (2011)
1-D nanostructure network of tin oxide has advantages in dye-sensitized solar cell because of its direct charge transport channel, higher electron mobility and better long-term stability, compared with the conventionally used TiO2 nanoparticle. This project focuses on growth of tin oxide 1-D nanostructure network via Vapor-liquid-solid method and study the application of tin oxide material in dye-sensitized solar cell. Tin oxide and graphite mixed powders were used as source material to grow nanowires with different lengths and diameters on gold-catalysed substrates. SEM, Alpha surface profiler, EDX and XRD were used to characterize the nanowire film morphology, thicknesses, nanowire diameters, compositions and crystal structures.